2020
DOI: 10.4149/av_2020_311
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating miR-494 in plasma of children with enterovirus 71 induced hand, foot, and mouth disease and its potential diagnostic value

Abstract: hand, foot, and mouth disease (hFMD) is a common pediatric disease, whose outcome depends of the enterovirus genotype infecting the patient. The present study is focused on the potential diagnostic value and the role of circulating microRNA-494 (miR-494) in enterovirus 71-induced more severe form of hFMD. We included 102 children with enterovirus 71 (EV71)-induced hFMD, 42 coxsackievirus A16 (CA16)-induced hFMD and 102 healthy controls. The plasma and serum samples were collected. The expression level of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…(2011) reported that miR-545, miR-324-3p, and miR-143 can be used to effectively distinguish EV71 and CVA16 infections in patients with HFMD. Moreover, an investigation conducted by Liu et al. (2020) indicated that patients with EV71-induced HFMD presented significantly higher levels of serum miR-494 as compared with the level in healthy people or those with CVA16-induced HFMD, showing its potential diagnostic value.…”
Section: Potential Clinical Application Of Ncrnas In Hfmdmentioning
confidence: 99%
“…(2011) reported that miR-545, miR-324-3p, and miR-143 can be used to effectively distinguish EV71 and CVA16 infections in patients with HFMD. Moreover, an investigation conducted by Liu et al. (2020) indicated that patients with EV71-induced HFMD presented significantly higher levels of serum miR-494 as compared with the level in healthy people or those with CVA16-induced HFMD, showing its potential diagnostic value.…”
Section: Potential Clinical Application Of Ncrnas In Hfmdmentioning
confidence: 99%
“…Notably, EV71 infection leads to a marked increase in the release of circulating IL-6. And the level of IL-6 gradually rises with the progression of the disease and is associated with poor prognosis of patients infected with EV71 [145] , [146] . Among severe and critical cases infected with EV71 undergoing intravenous immunoglobulin (IVIG) and glucocorticoid treatment, convalescent patients have a significantly lower level of IL-6 in cerebrospinal fluids than acute stage patients [147] .…”
Section: Roles Of Il-6-mediated Immunometabolic Reprogramming In Vira...mentioning
confidence: 99%